Concrete mix design, quality control and specification - Day, Ken W. ([S.l.] : CRC Press, 2006)
This new edition of Ken Day's established professional guide provides comprehensive, readily understandable assistance to concrete producers in the design and control of their product, and looks as far as possible into the future of concrete. Concrete has become a complex material, generating hundreds, if not thousands, of PhD theses and a substantial number of computerised systems. Having originated the first of such systems, Ken Day now shows how to apply the principles with or without elaborate systems. Such systems pay big dividends to the larger producer but this book still shows the small producer how to achieve competitive mix designs and close quality control without either excessive expenditure or extensive theoretical study. The accompanying website, www.kenday.id.au, offers free programs and access to continually updated advice.